The Concept of Jihad in Qutb and Shari’ati - Mohamed, Yasien (Afkar: Jurnal Akidah dan Pemikiran Islam, 2009)
This article will compare the concept of jihad of two contemporary Islamic radical figures, the Egyptian Sayyid Qutb (d. 1966) and the Iranian ‘Ali Shari’ati (1977). It will place the concept within the context of the life and works of these two Islamic thinkers. Both Qutb and Shari’ati shaped the view of Islam as an instrument of social change, and presented it as an alternative to Capitalism and Communism. They both shared the vision of Islam as a political movement, and while they opposed the secular nationalism that had dominated the 1960s, they also rejected the traditional Sunni or Shi’ite view that relegated political jihad to a secondary concern. They broke away from the established order that espoused the nationalist goals of the time, attracted a new generation of Muslim youth, and alienated the ulema. Qutb and Shari’ati reactivated Islam as the political standard for Muslim behaviour. The essay will also contrast key concepts such as Islam and Jahiliyyah in Qutb and tawhīd and shirk in Shari’ati in order to demonstrate the dialectical character of their concept of jihad.